INFLUENCE OF THE TYPE OF INSERTS ON DIMENSIONAL ACCURACY IN TURNING PROCESS - Pavel POLÁK; Ján ŽITŇANSKÝ; Michal ADAMIK (Management Systems in Production Engineering, 2015)
This article is aimed to demonstrate the effect of cutting material and geometry of inserts chip breaker for dimensional accuracy in turning. The experiment is aimed on measuring compliance with dimensional accuracy in turning of samples from steel 11 523 at a constant feed rate and depth of cut, with varying spindle speeds. Machining was performed by using a different types of replaceable inserts. The measurement results will be evaluated in terms of the impact of differ-ent geometry characteristics and changing speeds spindle.